Pengaruh Literasi Ekonomi Syariah terhadap Minat Mahasiswa Menabung di Bank Syariah - Firdiana, Erika; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2021)
The purpose of this research was to understand whether or not Islamic economics literacy influence college students saving interest in Islamic bank. The sampling technique used in purposive sampling technique with a population of study is college student of sharia economics, sharia banking, Islamic economics and sharia accounting major or study program in East Java which is calculated using the convenience formula. The study used a quantitative research method with questionnaire as the primary data. In testing the hypothesis used simple linier regression analysis techniques. So The result obtained shows that Islamic economics literacy has positive and significant influence to the college students saving interest in Islamic bank with significance value of 0,000 < 0,005 with regression equation as Y = 1,118 + 0,227X.